Analisis Pelaksanaan Rujukan Pasien Rawat Jalan Peserta BPJS Kesehatan di Puskesmas Mataram - Yasa, I Gede; Sulaiman, Lalu; Karjono, Karjono (Bioscientist : Jurnal Ilmiah Biologi, 2024)
The referral system is a healthcare management system that carries out the transfer of mutually accountable responsibilities for a specific medical case or health problem either vertically, meaning from a less capable unit to a more capable unit, or horizontally, meaning among units of similar capabilities. The referral system regulates the flow of where someone with a particular health problem should seek examination for their health issues. The purpose of this research is to analyze the Implementation of Outpatient Referral for Participants of the Health Social Security Agency (BPJS Kesehatan) at Mataram Community Health Center. The method used in this research employs a qualitative descriptive approach to gain an overview of the analysis of outpatient referral implementation for BPJS Kesehatan participants at Mataram Community Health Center. Descriptive means that the data collected are in the form of words, images, and not numerical values. The findings of the research indicate that the implementation of outpatient referral at the Community Health Center shows that it has not fully run smoothly. Patient knowledge varies, with some understanding and others not understanding. The facilities and infrastructure are still lacking, some diseases diagnosed under code 144 are still referred, many referrals are initiated by the patients themselves, and there are outpatient referrals from outside healthcare facilities.